AMEE Consensus Statement: Planetary health and education for sustainable healthcare. (4th March 2021) - Shaw, Emily; Walpole, Sarah; McLean, Michelle; Alvarez-Nieto, Carmen; Barna, Stefi; Bazin, Kate; Behrens, Georgia; Chase, Hannah; Duane, Brett; El Omrani, Omnia; Elf, Marie; Faerron Guzmán, Carlos A.; et al.
Abstract: The purpose of this Consensus Statement is to provide a global, collaborative, representative and inclusive vision for educating an interprofessional healthcare workforce that can deliver sustainable healthcare and promote planetary health. It is intended to inform national and global accreditation standards, planning and action at the institutional level as well as highlight the role of individuals in transforming health professions education. Many countries have agreed to 'rapid, far-reaching and unprecedented changes' to reduce greenhouse gas emissions by 45% within 10 years and achieve carbon neutrality by 2050, including in healthcare. Currently, however, health professions graduates are not prepared for their roles in achieving these changes. Thus, to reduce emissions and meet the 2030 Sustainable Development Goals (SDGs), health professions education must equip undergraduates, and those already qualified, with the knowledge, skills, values, competence and confidence they need to sustainably promote the health, human rights and well-being of current and future generations, while protecting the health of the planet. The current imperative for action on environmental issues such as climate change requires health professionals to mobilize politically as they have before, becoming strong advocates for major environmental, social and economic change. A truly ethical relationship with people and the planet that we inhabit so precariously, and to guarantee a future for the generations which follow, demands nothing less of all health professionals. This Consensus Statement outlines the changes required in health professions education, approaches to achieve these changes and a timeline for action linked to the internationally agreed SDGs. It represents the collective vision of health professionals, educators and students from various health professions, geographic locations and cultures. 'Consensus' implies broad agreement amongst all individuals engaged in discussion on a specific issue, which in this instance, is agreement by all signatories of this Statement developed under the auspices of the Association for Medical Education in Europe (AMEE). To ensure a shared understanding and to accurately convey information, we outline key terms in a glossary which accompanies this Consensus Statement (Supplementary Appendix 1). We acknowledge, however, that terms evolve and that different terms resonate variably depending on factors such as setting and audience. We define education for sustainable healthcare as the process of equipping current and future health professionals with the knowledge, values, confidence and capacity to provide environmentally sustainable services through health professions education . We define a health professional as a person who has gained a professional qualification for work in the health system, whether in healthcare delivery, public health or a management or supporting role and education as ' the system comprising structures, curricula, faculty and activities contributing to a learning process' . This Statement is relevant to the full continuum of training – from undergraduate to postgraduate and continuing professional development.